The Relationship Between the Level of Student Participation in Organizations and Academic Achievement - Mariah; Nurhakim, Putri Rahmah; Cutwan Nurul; Marna Sani; Fetri Mulia Sari; Fina Selfia (Indonesian Journal of Teaching and Teacher Education, 2023)
This research has high urgency because it explores the relationship between student participation in student organizations and academic achievement, especially in Sociology students at Teuku Umar University. Academic success and the role of organizations in achieving it are very important to improve the quality of education. The belief that active participation in organizations can shape time management and influence positive learning outcomes is the main basis for this study. Evaluation of previous studies revealed shortcomings in methods, research focus, and quality of results which this study addresses through quantitative methods and a focus on sociology students. This approach makes a significant contribution to understanding the relationship between student participation in organizations and academic achievement. Using questionnaires, observations, and interviews, this study explains the extent of the relationship between the variables of participation and academic achievement through simple linear regression. The results of the study provide a deeper understanding of the influence of student participation in student organizations on student academic achievement. Implications may form the basis of campus policies and practices to enhance students' experiences and support their success in various aspects of campus life. This research makes a significant contribution in filling the existing knowledge gap and stimulating further research